Tuturan Ekspresif Dalam Novel Densha Otoko Karya Nakano Hitori - Aimee Aristia Wulandari, Kadek; Anggraeny, Renny (Humanis, 2017)
This undergraduate thesis entitled expressive speech in novel Densha Otoko by Nakano Hitori. The theory used in this research is the theory of speech acts proposed by Searle (1969). The method used to collect data in this research is observation method. In the data analysis the method used is the pragmatic approach method. On the presentation stage of data analysis, it uses the informal methods.The analysis results showed that in Densha Otoko novel, there were 14 types of expressive speech. 1) thanking, 2) praising, 3) criticizing, 4) blaming, 5) expressing sympathy, 6) congratulating, 7) complain, 8) pardoning, 9) rating, 10) expressing embarassement, 11) Expressing shock feeling,    12) kidding, 13) greeting, and 14) farewell. Perlocutionary act of expressive speech contained in the novel Densha Otoko is not only generated by speakers to influence the hearers, however the speakers sometimes only express expressive speech with declarative sentence mode. This is because speakers are only express expressive speech, which only declared what the speakers felt and there are no perlocutionary act generated in the speech such as, arigatou gozaimasu, which means thank you.